Population Evolution, Genetic Diversity and Structure of the Medicinal Legume, Glycyrrhiza uralensis and the Effects of Geographical Distribution on Leaves Nutrient Elements and Photosynthesis - Dang, Hanli; Zhang, Tao; Li, Yuanyuan; Li, Guifang; Zhuang, Li; Pu, Xiaozhen (Frontiers in Plant Science, 2022)
Glycyrrhiza uralensis is a valuable medicinal legume, which occurs widely in arid and semi-arid regions. G. uralensis demand has risen steeply due to its high medical and commercial value. Interpret genome-wide information can stimulate the G. uralensis development as far as its increased bioactive compound levels, and plant yield are concerned. In this study, leaf nutrient concentration and photosynthetic chlorophyll index of G. uralensis were evaluated to determine the G. uralensis growth physiology in three habitats. We observed that G. uralensis nutrient levels and photosynthesis differed significantly in three regions (P < 0.05). Whole-genome re-sequencing of the sixty G. uralensis populations samples from different habitats was performed using an Illumina HiSeq sequencing platform to elucidate the distribution patterns, population evolution, and genetic diversity of G. uralensis. 150.06 Gb high-quality clean data was obtained after strict filtering. The 895237686 reads were mapped against the reference genome, with an average 89.7% mapping rate and 87.02% average sample coverage rate. A total of 6985987 SNPs were identified, and 117970 high-quality SNPs were obtained after filtering, which were subjected to subsequent analysis. Principal component analysis (PCA) based on interindividual SNPs and phylogenetic analysis based on interindividual SNPs showed that the G. uralensis samples could be categorized into central, southern, and eastern populations, which reflected strong genetic differentiation due to long periods of geographic isolation. In this study, a total of 131 candidate regions were screened, and 145 candidate genes (such as Glyur001802s00036258, Glyur003702s00044485, Glyur001802s00036257, Glyur007364s00047495, Glyur000028s00003476 and Glyur000398s00034457) were identified by selective clearance analysis based on Fst and θπ values. Gene Ontology (GO) and KEGG pathway analysis showed significant enrichment of 110 GO terms including carbohydrate metabolic process, carbohydrate biosynthetic process, carbohydrate derivative biosynthetic process, and glucose catabolic process (p < 0.05). Alpha-linolenic acid metabolism, biosynthesis of unsaturated fatty acids, and fatty acid degradation pathways were significantly enriched (p < 0.05). This study provides information on the genetic diversity, genetic structure, and population adaptability of the medicinal legumes, G. uralensis. The data obtained in this study provide valuable information for plant development and future optimization of breeding programs for functional genes.